Abu Rayhan Beruni's Humanistic Ideas And Their Expression In His Scientific Legacy (The Peerian Journal, 2025)
This article analyzes the humanistic ideas embodied in the scientific heritage of the great scholar and thinker Abu Rayhan Beruni. The article reveals Abu Rayhan Beruni's humanistic approaches based on his views on science, human potential, and intercultural dialogue. It also examines the principles related to the exaltation of human dignity, values, and rights in his philosophical, natural-scientific, and ethical views